Cigarette Smoking and Activities of Daily Living in Ocular Myasthenia Gravis. Issue 1 (March 2016) - Gratton, Sean M.; Herro, Angela M.; Feuer, William J.; Lam, Byron L.
Abstract : Background: Myasthenia gravis is an autoimmune disease of the neuromuscular junction, commonly affecting the ocular muscles. Cigarette smoking has been shown to influence many autoimmune diseases, including multiple sclerosis and rheumatoid arthritis, but its effect on myasthenia gravis has not been well studied. We sought to determine whether cigarette smoking influenced disease-related symptoms in ocular myasthenia gravis (OMG). Methods: We performed a prospective, clinic-based cross-sectional study in a single academic neuro-ophthalmology practice. All patients diagnosed with OMG between November 2006 and April 2014 were included. A prospective telephone survey was administered to determine smoking status and myasthenia gravis-related symptom severity. The main outcome measure was the myasthenia gravis-specific activities of daily living (MG-ADL) score, a well-validated marker of symptoms and quality of life in myasthenia gravis. Results: Forty-four patients were included in the analysis. Comparison of MG-ADL ocular subscores between current smokers (3.4 ± 2.6), former smokers (1.8 ± 2.1), and never smokers (1.1 ± 1.5) revealed a statistically significant relationship ( P = 0.031) where current smokers had the highest MG-ADL ocular subscores and never smokers the lowest. Comparison of MG-ADL total scores revealed the same relationship (current 5.6 ± 4.5, former 2.9 ± 3.1, never 1.4 ± 2.5, P = 0.003). There were borderline significant correlations of pack years with MG-ADL ocular subscore (r = 0.27, P = 0.074) and MG-ADL total score (r = 0.30, P = 0.051). Conclusions: Our findings indicate an association between cigarette smoking and symptom severity in OMG. This association suggests that smoking cessation in OMG patients may lead to improved symptom-related quality of life. Abstract : Supplemental Digital Content is Available in the Text.